Auditing of Power Quality on Building G5 of Universitas Muhammadiyah Yogyakarta - Agus Jamal; Slamet Suripto; Rama Okta Wiyagi; Dimas Bangkit Wijayanto; Yessi Jusman; Teguh Iman Prasetyo (Universitas Muhammadiyah Yogyakarta, 2019)
Universitas Muhammadiyah Yogyakarta, as an educational institution, indeed uses the building as a supporting facility for all activities carried out. In each of the reviews, these activities, of course, use of electrical energy, but not infrequently the electrical energy used exceeds the limits of the reasonableness of the resulting use in financial swelling. An energy audit is an activity carried out periodically to determine the amount of energy consumption, irregularities in the system, and load imbalances that cause power losses in a building. These parameters can be obtained by measuring on the SDP panel using a power quality analyzer with IEEE 59-1992 as a obtained reference to the results of the average voltage fluctuations are still within the safe limits determined by PLN items, i.e., from 198 to 231 volts. THDv is still within the safe limit under 5%, as well as for the THDi is also still within the safe limit of tolerance of 15%. As a result of harmonic disturbances and load imbalances in the building G5 in 2018, the caused losses of power losses that need to be borne by Universitas Muhammadiyah Yogyakarta in the amount of Rp 9,210,133.09.